Pelatihan Pembelajaran STEM untuk Mendukung Implementasi Kurikulum Merdeka pada Proyek Merancang Filter Air - Nurul Fitriyah Sulaeman; Atin Nuryadin; Greny Mispi Anisa Sari; Agus Riyadi; Feby Zulhiyah; Desi Az Zahra Putri; Muhammad Ikhsan Bachrul Alam (Bubungan Tinggi: Jurnal Pengabdian Masyarakat, 2023)
Tujuan pelatihan pembelajara STEM adalah meningkatkan kemampuan guru merancang pembelajaran STEM dalam implementasi kurikulum Merdeka. Peserta pelatihan merupakan 35 Guru IPA SMP Kota Bontang dan tempat pelaksanaan pengabdian di Autis Center, Kota Bontang. Pelatihan pembelajaran STEM ini dilaksanakan pada tanggal 14-18 Februari 2023 sebanyak 17 JP, serta memiliki tujuan agar guru dapat lebih mengenal pembelajaran STEM pada kurikulum Merdeka dan tentunya guru IPA SMP Kota Bontang dapat menerapkan pendekatan STEM dalam pembelajaran. Hasil dari pelatihan yaitu, guru mampu menyusun perangkat pembelajaran STEM efektif sesuai dengan capaian pembelajaran pada kurikulum Merdeka pada materi filter air. Hal ini terlihat pada hasil respon dari peserta pelatihan mencapai 90% baik dan pendapat dari peserta bahwa pelatihan sangat bermanfaat dan lebih mengenal pembelajaran STEM. Hasil ini menunjukkan urgensi dilakukannya pelatihan guru IPA secara berkala.Transitioning from the Indonesian curriculum to the Merdeka Curriculum is challenging for teachers. Teachers must be more creative in classroom learning through integrated learning in Science, Technology, Engineering, and Mathematics (STEM). However, teachers' knowledge and skills regarding STEM learning still need to be improved, so it is rare for teachers to use STEM learning. Therefore, efforts are made to overcome these problems by providing training on science learning using a STEM approach to support the implementation of the Merdeka curriculum. The training participants were 35 science teachers of SMP Bontang and the place of service at the Autism Center, Bontang City. This STEM learning training was carried out on 14-18 February 2023 with as many as 17 hours of lessons, and it aimed to make teachers more familiar with STEM learning in the Merdeka curriculum and able to apply the STEM approach in learning. The result of the training is that teachers can compile effective STEM learning tools following the learning outcomes in the Merdeka curriculum on water filter materials. This can be seen in the response results from training participants reaching 90% good and opinions from participants that the training is very useful and more familiar with STEM learning.